Negara Kesejahteraan dan Politik Pemenuhan Hak Sosial: Analisis Kebijakan Bantuan Langsung Tunai (BLT) di Kabupaten Tulungagung - Fauzia, Marliana Eka; Purnawati, Laily (Universitas Brawijaya, 2025)
This study analyzes the cash transfer assistance (BLT) policy in Tulungagung Regency through Esping-Andersen’s welfare state framework, focusing on decommodification, social rights, and social citizenship. Using a descriptive qualitative approach based on official documents, BPS data, and recent literature, the study finds that BLT reflects a residual and protective-selective welfare model with partial decommodification. The effectiveness of BLT is shaped by local governance capacity and the sustainability of regional funding. This study contributes by contextualizing welfare state theory within local decentralization.